2015
DOI: 10.1136/neurintsurg-2014-011643
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable neurological outcome in diabetic patients with acute ischemic stroke is associated with incomplete recanalization after intravenous thrombolysis

Abstract: Diabetic patients with AIS had unfavorable neurological outcome, potentially linked to incomplete recanalization after IVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Although there is some conflicting evidence in studies of people with ischemic 13,14,51 and hemorrhagic stroke 38 , diabetes is typically associated with poorer functional outcome 8,12,26,27,50,55 , especially in poorly controlled diabetes (HbA1c >7%) 91 . Diabetes has also been associated with worse neurological deterioration (decrease of National Institute of Health Stroke Scale points <4 at 24 h, or <8 at day 7), poorer recovery (mRS >1 at 3 months) and increased risk of hemorrhagic development 72 in people treated with thrombolysis for ischemic stroke 56 . An explanation for this might be incomplete recanalization after thrombolysis, as suggested in one study 92 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is some conflicting evidence in studies of people with ischemic 13,14,51 and hemorrhagic stroke 38 , diabetes is typically associated with poorer functional outcome 8,12,26,27,50,55 , especially in poorly controlled diabetes (HbA1c >7%) 91 . Diabetes has also been associated with worse neurological deterioration (decrease of National Institute of Health Stroke Scale points <4 at 24 h, or <8 at day 7), poorer recovery (mRS >1 at 3 months) and increased risk of hemorrhagic development 72 in people treated with thrombolysis for ischemic stroke 56 . An explanation for this might be incomplete recanalization after thrombolysis, as suggested in one study 92 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between diabetes and neurological outcome is summarized in Table 1. Six studies 12,26,50,[55][56][57] showed an association between diabetes and poorer neurological outcome, whereas four studies 8,13,14,38 did not show a difference. Between these studies, the outcome measures used were the modified Rankin scale (mRS) 8,14,26,38,50,[55][56][57] , Functional Independence Measure 12,13 and the Scandinavian stroke scale 14 .…”
Section: Diabetes and Outcomes After Strokementioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that stroke severity and serum glucose level had a significant influence on intracerebral hemorrhage after intravenous tissue plasminogen activator therapy [22][23][24]40], which was consistent with our findings, even though we used SSI as a substitute for NIHSS score as a measure of stroke severity. In addition to the glucose level, diabetes may be associated with poor outcome of rt-PA therapy [41,42]. One study found that in the diabetic subgroup, the glycated hemoglobin index was positively correlated with symptomatic intracranial hemorrhage [40].…”
Section: Discussionmentioning
confidence: 99%
“…DM has been associated with a significantly higher incidence of death [2][3][4][5] , dependency [4,6] and recurrent stroke [3,7] and with an increased risk of intracerebral hemorrhage following thrombolysis (OR 3.61) after stroke [8] , which becomes higher in those with poor glycemic control [9] . Our recent study of 419 acute stroke patients demonstrated that intravenous thrombolysis failed to improve outcome in patients with DM, which was also shown to be associated with incomplete recanalization after thrombolysis (OR 0.268) in patients with large vessel occlusion [10] .…”
mentioning
confidence: 99%